Bibliometric Analysis: Research Trends of Raspberry Pi-Based Egg Incubators in the Last Ten Years (2013-2022) - Meta Yantidewi; Jhulinda Nizar Wati; Utama Alan Deta (IKIP Mataram, 2023)
Technological developments that continue to increase provide an impetus for scientists to conduct research, One of them is the field of animal husbandry and instrumentation by making Raspberry Pi-based egg incubators. A device that replicates an incubator by keeping eggs at the right humidity uses a Raspberry Pi microcontroller to incubate the eggs. This research objective is to find out how far the development of the number of international publications using the Google Scholar database and to find out the development map of international research publications based on keywords. Data collection by searching Google Scholar with the keywords